Twist-bend nematics, liquid crystal dimers, structure–property relations. Issue 1 (2nd January 2017) - Dawood, Alya A.; Grossel, Martin C.; Luckhurst, Geoffrey R.; Richardson, Robert M.; Timimi, Bakir A.; Wells, Neil J.; Yousif, Yousif Z.
ABSTRACT: One of the current challenges in liquid crystal science is to understand the molecular factors leading to the formation of the intriguing twist-bend nematic phase (NTB ) and determine its properties. During our earlier hunt for the NTB phase created on cooling directly from the isotropic phase and not the nematic phase, we had prepared 30 symmetric liquid crystal dimers. These had odd spacers and methylene links to the two mesogenic groups; desirable but clearly not essential features for the formation of the NTB . Here, we report the phases that the dimers exhibit and their transition temperatures as functions of both the lengths of the spacer and the terminal chains. In addition we describe the transitional entropies, their optical textures, the X-ray scattering patterns and the 2 H NMR spectra employed in characterising the phases. All of which may lead to important properties of the twist-bend nematic phase. Graphical Abstract: